Analysis of Students’ Problem in Speaking at Junior High School 2 Mirit Kebumen - Septiana, Catur; Dewi, Puspa; Masykuri, Edi Sunjayanto (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Basic skills that indicate proficiency in English are proficiency in the language. Most students have difficulty in speaking English. Therefore, the purpose of this study is to identify the problems faced by students when learning English, especially those related to speaking skills. In today's era of globalization, English language skills are becoming increasingly important. However, students in junior high schools often need help to speak English fluently. One of the most important initial steps in dealing with the problem of teaching English in junior high schools is to understand and analyze the difficulties faced by students. This research was conducted at SMP Negeri 2 Mirit, with 1 English teacher and 7th grade C students as participants. This research used interview and observation techniques to find out the problems faced by students when speaking in English learning.